Conflicting obligations in human social life. (30th April 2020) - Hirsh, Jacob B.; Shteynberg, Garriy; Gelfand, Michele J.
Abstract: Tomasello describes how the sense of moral obligation emerges from a shared perspective with collaborative partners and in-group members. Our commentary expands this framework to accommodate multiple social identities, where the normative standards associated with diverse group memberships can often conflict with one another. Reconciling these conflicting obligations is argued to be a central part of human morality.